Infección pulmonar por una mycobacterium kansassi en paciente con fibrosis pulmonar idiopática. - Meneses Martínez, Nelly Maribel (2020)
Infection caused by the bacteria Mycobacterium kansasii. Those bacteria can be found in water, dirt, and food. Mycobacterium kansasii usually infects the lungs, but it can also infect other organs. For the most part, people with healthy immune systems are not affected by bacteria. In people with HIV, extrapulmonary infection with Mycobacterium kansasii or that which has spread is a characteristic condition of AIDS. There are about 140 species of nontuberculous mycobacteria and they have been linked to a very wide variety of infections. In this case, it involves a 79-year-old patient who goes to the hospital due to a general malaise but not achieving improvement, it is done in microscopic study and sputum tests and it is achieved that it was a mycobacterium kansassi, a timely diagnosis and adequate treatment.